ChemInform Abstract: Bioactive Norditerpenoids from Flickingeria fimbriata. Issue 48 (2nd December 2014) - Chen, Jin‐Long; Zhao, Zhi‐Min; Xue, Xue; Tang, Gui‐Hua; Zhu, Long‐Ping; Yang, De‐Po; Jiang, Lin
Abstract Seven new degraded diterpenoids [e.g. (IIa), (III), (IV)], four new ent‐pimarane type diterpenoids [e.g. (I)], and a known analog are isolated from the title stem.